Aktivitas Analgetika dan Antiinflamasi Ekstrak Etanol dan Fraksi Daun Jambu Mawar (Syzygium jambos L.) Secara In Vivo: Analgetic and Anti-inflammatory Activity of Ethanol Extract and Fraction of Guava Leaf (Syzygium jambos L.) In Vivo - Deden Winda Suwandi; Tita Puspita; Doni Anshar Nuari; Syifa Hamdani (Jurnal Sains dan Kesehatan, 2021)
Syzygium jambos is a plant that has traditionally been used to treat several diseases, especially the leaves as a medicine for rheumatism. In this study, the ethanol extract, fraction of n-hexane, ethyl acetate, and water from its leaves were tested for analgesic and anti-inflammatory activity using the writhing method (Siegmund), hot plate, and the formation of swelling of the soles induced by carrageenan lamda. The results showed that the ethanol extract at doses of 100 and 200 mg/kg BW and fractions of n-hexane, ethyl acetate and water at doses of 50 and 100 mg/kg BW had analgesic and anti-inflammatory activities. The ethanol extract at doses of 100 and 200 mg/kg BW can reduce the amount of writhing every 5 minutes for 60 minutes of observation by 84 and 98 times with percent protection of 58.0 and 52.0%. The Ethyl acetate, n-hexane, and water fractions of 50 and 100 mg/kg BW can reduce the amount of animal writhing by 93 and 35 times, 75 and 100 times, as well as 84 and 124 times with the percent of protection is 54.45 and 82.85, 63.0 and 50.9, as well as 58.47 and 38.02%. The analgesic activity of the hot plate method, ethanol extract can increase the survival time of animals in the hot plate by 154.0 and 95.02%, while the animal survival time of the n-hexane fraction is 95.86 and 105.5, ethyl acetate by 143, 7 and 105.7, and the water fraction of 34.1 and 99.5%. The anti-inflammatory activity of ethanol extract at doses of 100 and 200 mg/kg BW was indicated by a decrease in the volume of rat leg edema at the time of observation for 6 hours with the percent inhibition of edema of 59.2 and 41.12%. The n-hexane, ethyl acetate, and water fractions have relatively the same ability, indicated by the edema inhibition value of the n-hexane fraction of 68.24 and 68.56%, the ethyl acetate fraction of 57.08 and 67.32% and the fraction water of 64.02 and 67.46%. The effective dose of extracts and fractions of n-hexane, ethyl acetate, and water as analgesics and anti-inflammatory is 100 mg/kg BW.